2008
DOI: 10.1016/j.molcel.2008.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Mediator Links Epigenetic Silencing of Neuronal Gene Expression with X-Linked Mental Retardation

Abstract: SUMMARY Mediator occupies a central role in RNA polymerase II transcription as a sensor, integrator, and processor of regulatory signals that converge on protein-coding gene promoters. Compared to its role in gene activation, little is known regarding the molecular mechanisms and biological implications of Mediator as a transducer of repressive signals. Here, we describe a protein interaction network required for extra-neuronal gene silencing comprising Mediator, G9a histone methyltransferase, and the RE1 sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
240
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(249 citation statements)
references
References 57 publications
6
240
0
Order By: Relevance
“…Missense mutations of MED12 are associated with X-linked genetic syndromes [103][104][105]. Somatic mutations have been described in many solid tumors, including, hormone-associated cancers (prostate and adrenocortical carcinoma) [106,107], breast [108], uterine tumors [109].…”
Section: Med12 Mutationsmentioning
confidence: 99%
“…Missense mutations of MED12 are associated with X-linked genetic syndromes [103][104][105]. Somatic mutations have been described in many solid tumors, including, hormone-associated cancers (prostate and adrenocortical carcinoma) [106,107], breast [108], uterine tumors [109].…”
Section: Med12 Mutationsmentioning
confidence: 99%
“…Med12 promotes the epigenetic silencing of target genes by recruiting a histone methyltransferase and methylating chromatin (Ding et al, 2008). In Arabidopsis, Med12 (CENTER CITY [CCT]) and Med13 (GRAND CENTRAL [GCT]) exert a transient repression on the transcriptional machinery that interferes with embryo development (Gillmor et al, 2010).…”
Section: Expression Profile Of the Kinase Module And Other Associatedmentioning
confidence: 99%
“…As a component of the kinase module, MED12 can interact with G9a methyltransferase to induce histone methylation and thereby represses gene transcription (Ding et al, 2008). This function of MED12 is considered as an additional mechanism by which the kinase module negatively regulates the activity of the Mediator Complex.…”
Section: The Biological Functions Of Med12mentioning
confidence: 99%
“…MED12 bridges REST to G9a-dependent histone H3K9 dimethylation to suppress neuronal genes in non-neuronal cells. Mutations in MED12 found in FG and Lujan syndromes disrupt the REST repressor function, implicating that MED12-associated mental retardation involves impaired REST-dependent neuronal gene regulation (Ding et al, 2008). Very recently, Lai et al reported that MED12 interacts with a special class of activating long noncoding RNA (ncRNA-a) to regulate target gene expression.…”
Section: The Biological Functions Of Med12mentioning
confidence: 99%